Benchmarking tactical efficiency in international football: Identifying gaps and strategic improvements - Hwang, H. (Journal of Human Sport & Exercise, 2025)
This study evaluates the tactical efficiency of the South Korean national football team using a modified output-oriented BCC Data Envelopment Analysis (DEA) model, by benchmarking its performance against reference teams grouped by continental classifications. Among the four reference groups, America and Europe group produced feasible solutions. South Korean national football team consistently underperformed in converting tactical inputs into goals. In several cases indicating that the team would need to double its goal output - given its current resource level - to match benchmark efficiency. This research contributes methodologically by reinterpreting Ø as a goal-scaling factor and slack variables as diagnostics for tactical inefficiencies. As such, DEA proves valuable not only for internal efficiency evaluation but also for strategic benchmarking in high-performance football contexts. This study offers a DEA-based framework to evaluate tactical efficiency by comparing teams` resource usage and outcomes across formations and tournament stages. It benchmarks the target team against efficient team combinations to identify tactical gaps and input shortfalls. The findings provide strategic guidance by quantifying areas for improvement and suggesting optimal resource.